2008
DOI: 10.1111/j.1743-6109.2007.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chloride Channels in the Regulation of Corpus Cavernosum Tone: A Potential Therapeutic Target for Erectile Dysfunction

Abstract: Introduction Recent electrophysiological recordings have identified the existence of outward, excitatory chloride (Cl−) currents in rat, rabbit, and human corpus cavernosum (CC) muscle cells. Aim The aim of this study was to investigate the physiological role of Cl− currents in the maintenance of cavernosal muscle tone in isolated rabbit CC tissues. Methods C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
3
13
0
1
Order By: Relevance
“…The dual patch clamp/ Ca 2+ imaging recordings in the present study demonstrated that each Ca 2+ wave was indeed associated with a substantial Clcurrent, suggesting that one of the functions of the waves is to stimulate the cell via membrane depolarization. This mechanism is likely to play a role in propagating the Ca 2+ signal across the syncytium in the whole tissue and is consistent with the increasing evidence that Clchannels are important for maintaining detumescent tone [14,24]. The Clchannel-mediated depolarization would also provide a suitable mechanism for activation of voltage-dependent Ca 2+ channels which have been shown to be important for contraction [11,12].…”
Section: Discussionsupporting
confidence: 78%
“…The dual patch clamp/ Ca 2+ imaging recordings in the present study demonstrated that each Ca 2+ wave was indeed associated with a substantial Clcurrent, suggesting that one of the functions of the waves is to stimulate the cell via membrane depolarization. This mechanism is likely to play a role in propagating the Ca 2+ signal across the syncytium in the whole tissue and is consistent with the increasing evidence that Clchannels are important for maintaining detumescent tone [14,24]. The Clchannel-mediated depolarization would also provide a suitable mechanism for activation of voltage-dependent Ca 2+ channels which have been shown to be important for contraction [11,12].…”
Section: Discussionsupporting
confidence: 78%
“…However, the idea that corpus cavernosum cells maintain a constantly high Ca 2+ by remaining depolarized within the window current range of potentials is at odds with a number of observations (see Introduction). There is growing evidence that Ca 2+ ‐activated Cl – currents are essential for maintaining corpus cavernosum tone, and that these currents are activated in response to oscillatory changes in intracellular Ca 2+ [12–15,25,26]. Calcium waves, similar to those reported here, were shown to activate the Cl – current in isolated rabbit corpus cavernosum myocytes [15].…”
Section: Discussionsupporting
confidence: 76%
“…The waves depended on an intact sarcoplasmic reticulum Ca 2ϩ store, because they were blocked by cyclopiazonic acid and agents that interfere with ryanodine receptors and IP 3 -mediated Ca 2ϩ release. Chu and Adaikan (2008) underlined the importance of Cl Ϫ currents as a mechanism in the maintenance of CC tone produced by adrenergic and various endogenous constrictors in strips of rabbit CC. They suggested that the modulation of Cl Ϫ1 current could be an attractive and effective approach to regulate penile erection.…”
Section: B K ϩ Channelsmentioning
confidence: 99%
“…The contribution of chloride channels/currents to the modulation of human corporal smooth muscle tone is less well understood than that of the other ion channels. Studies of calcium-activated Cl Ϫ (Cl Ca ) function in the smooth muscle of CC have shown these channels to be involved in both the maintenance of spontaneous tone and the contractile response to noradrenaline and other agonists (Fan et al, 1999;Karkanis et al, 2003;Craven et al, 2004;Williams and Sims., 2007;Chu and Adaikan, 2008;Chung et al, 2009b). Karkanis et al (2003) demonstrated an excitatory calcium Cl Ca current in both human and rat corporal myocytes.…”
Section: B K ϩ Channelsmentioning
confidence: 99%